Effect of oleic acid supplementation on prostaglandin production in maternal endometrial and fetal allantochorion cells isolated from late gestation ewes. Issue 9 (September 2015) - Cheng, Z.; Abayasekara, D.R.E.; Elmes, M.; Kirkup, S.; Wathes, D.C.
Abstract Introduction Elevated circulating non-esterified fatty acids including oleic acid (OA) are associated with many pregnancy related complications. Prostaglandins (PGs) play crucial roles during parturition. We investigated the effect of OA supplementation on PG production using an in vitro model of ovine placenta. Methods Maternal endometrium (ME) and fetal allantochorion (FC) were collected in late pregnancy (day 135). Confluent cells were cultured in serum-free medium supplemented with 0, 20 or 100 μM OA and challenged with control medium, oxytocin (OT, 250 nM), lipopolysaccharide (LPS, 0.1 μg/ml) or dexamethasone (DEX, 5 μM). Spent medium was harvested at 2 and 24 h after challenge for quantifying PGs. Results In ME cells OA increased PGE2 production moderately but attenuated PGF2α production leading to a doubling of the PGE2:PGF2α ratio (E:F) (P < 0.01). Without OA, both OT and LPS stimulated PG production for about 3-fold (P < 0.01) without changing the E:F ratio. In the ME cells challenged with OT, OA decreased both PGE2 and PGF2α production by up to 70% (P < 0.01) whereas in LPS treated cells OA increased the E:F ratio. In FC cells PGE2 production at 2 h was stimulated by 100 μM OA (P < 0.05). In these cells LPS caused a 3-fold increase in PGE2 (P < 0.01), an effect which was completely inhibited by DEX. Discussion OA supplementation favours basal PGE2 production in both ME and FC. In ME OA increased E:F ratios and antagonized the stimulatory effect of OT on PG production. This suggests that raised circulating OA may affect both the initiation and progression of parturition.